2010
DOI: 10.3233/jad-2010-1277
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer Research Series on the Default Network

Abstract: CORTICAL CONNECTIONS GET CLOSER LOOK IN HEALTH, DISEASEThe idea of the default mode network, an interconnected set of brain regions that are active when the brain is resting and that power down during focused mental tasks, was first proposed in 2001, but it quickly became a hot topic in cognitive neuroscience and for Alzheimer's disease (AD) researchers. The seesaw activation and deactivation of the default network and task-related brain regions appears critical for peak performance on memory tasks and deactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…We were unable to infer individual DMN regions because fMRI is not performed as part of our hospital's personal health‐screening program. Because the same definition of the DMN area is used in many studies , we employed five DMN nodes based on this definition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were unable to infer individual DMN regions because fMRI is not performed as part of our hospital's personal health‐screening program. Because the same definition of the DMN area is used in many studies , we employed five DMN nodes based on this definition.…”
Section: Discussionmentioning
confidence: 99%
“…THE DEFAULT MODE NETWORK (DMN) has been the target of recent extensive research in the field of Alzheimer's disease (AD) . Hence, attempts have been made to apply resting‐state functional magnetic resonance imaging (RfMRI) as a noninvasive, readily available, and radiation‐exposure‐free biomarker of incipient AD .…”
mentioning
confidence: 99%
“…Although redefined as the manifestation of deteriorating brain functions over time as a part of aging due to cell deaths in the brain caused by neurodegeneration or any other disease (Peng, 2003), recent research showed that it is not only caused by neuronal cell death/loss, but rather by dysfunction and loss of synapses already occurring in early AD (Reddy et al, 2005) and in α-synucleinopathies, eg, Parkinson disease (PD) and dementia with Lewy bodies (DLB) (Schulz-Schaeffer, 2010), and by cholinergic neuronal and axonal abnormalities being present in aging and AD (Geula et al, 2008;Mufson et al, 2012). These changes induce disconnection of important nervous circuitries causing default networks (McCaffrey et al, 2010;Palop and Mucke, 2010;Pievani et al, 2011;Schroeter et al, 2012) that have been demonstrated in vivo in early AD (Wang et al, 2007), suggesting that disease progress is transmitted by neuronal pathways (Raj et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Oligomeric Aβ, for example, has been reported to disrupt phosphatidylinositol metabolism [121] and glutamate uptake [113]. Aβ aggregation in AD has moreover been associated with specific disturbance of the activity of the default network [122].…”
Section: Vh Finder / Alzheimer's Disease Introductionmentioning
confidence: 99%